Identifikasi Faktor Penyebab Grounding MV. Belik Mas pada Narrow Channel Kapuas River dengan Pendekatan Root Cause Analysis - Muhammad Setyan Farros Wa Savero; Anak Agung Istri Sri Wahyuni; Maulidiah Rahmawati; Dety Sutralinda (Pusat riset dan Inovasi Nasional, 2025)
Grounding or stranding is a shipping accident where the ship stops due to the lowest part of the ship's side or what is known as the keel touching the bottom of the water because the water depth is insufficient so that the ship cannot move freely. Grounding incidents occur more often in shallow waters or narrow shipping lanes. One of the grounding incidents was experienced by researchers while practicing sailing on the MV. Belik Mas, a container ship. At that time, the MV. Belik Mas ran aground when entering the Kapuas River Pontianak shipping lane. Therefore, this study aims to analyze the causes of the grounding of the MV. Belik Mas ship on the Kapuas River shipping lane and analyze the rescue efforts made. The method used in this study is a qualitative approach with the root cause analysis method which aims to identify the cause of the problem to the root cause. The results of the study showed that the root cause of the grounding of the MV. Belik Mas ship was human error, namely due to the lack of consideration in decision making by the captain and bad weather in the form of strong winds.